Advancing Science Education through Project-Based Learning: An Analytical Framework of Practical Applications for Indian Secondary Schools in Resource-Constrained Settings - Sharma, Anjali (International Journal Education and Computer Studies (IJECS), 2025)
This study looks at how Project-Based Learning (PBL) can be used in real life to improve science education in Indian secondary schools with limited resources. By qualitatively analyzing 111 Hindi-language science projects that follow the National Curriculum Framework, it reviewed three projects that are representative: biodegradable waste decomposition, plant morphology, and rust formation for their design pedagogical content scientific and feasibility. Results show that these inexpensive investigations relevant to the context help develop core competencies effectively such as observation data analysis collaborative inquiry and reasoning based on evidence. By merging learning through experience with relevance to the community, PBL closes the gap between instruction in theory and real scientific practice, even under conditions of resource constraint. In addition, PBL has shown potential for issues of gender and social equity by fostering inclusive participation and contextualized engagement. The study ends with the statement that scaling PBL across schools would need coherent policy alignment, teacher professional development, and reform in assessment practices to take science learning out of rote memorization into reflective inquiry-driven socially responsive education.